Differential Postoperative Effects of Volatile Anesthesia and Intraoperative Remifentanil Infusion in 7511 Thyroidectomy Patients: A Propensity Score Matching Analysis. Issue 7 (February 2016) - Jo, Jun-Young; Choi, Seong-Soo; Yi, Jung Min; Joo, Eun Young; Kim, Ji Hyun; Park, Se Ung; Sim, Ji-Hoon; Karm, Myong-Hwan; Ku, Seungwoo
Abstract : Abstract: Although remifentanil is used widely by many clinicians during general anesthesia, there are recent evidences of opioid-induced hyperalgesia as an adverse effect. This study aimed to determine if intraoperative remifentanil infusion caused increased pain during the postoperative period in patients who underwent a thyroidectomy. A total of 7511 patients aged ≥ 20 years, who underwent thyroidectomy between January 2009 and December 2013 at the Asan Medical Center were retrospectively analyzed. Enrolled patients were divided into 2 groups: group N (no intraoperative remifentanil and only volatile maintenance anesthesia) and group R (intraoperative remifentanil infusion including total intravenous anesthesia and balanced anesthesia). Following propensity score matching analysis, 2582 patients were included in each group. Pain scores based on numeric rating scales (NRS) were compared between the 2 groups at the postoperative anesthetic care unit and at the ward until 3 days postoperation. Incidences of postoperative complications, such as nausea, itching, and shivering were also compared. The estimated NRS pain score on the day of surgery was 5.08 (95% confidence interval [CI] 4.97–5.19) in group N patients and 6.73 (95% CI 6.65–6.80) in group R patients ( P  < 0 .001). There were no statistically significant differences in NRS scores on postoperative days 1, 2, and 3 between the 2 groups. Postoperative nausea was less frequent in group R (31.4%) than in group N (53.5%) ( P  < 0 .001). However, the incidence of itching was higher in group R (4.3%) than in group N (0.7%) ( P  < 0 .001). Continuous infusion of remifentanil during general anesthesia can cause higher intensity of postoperative pain and more frequent itching than general anesthesia without remifentanil infusion immediately after thyroidectomy. Considering the advantages and disadvantages of continuous remifentanil infusion, volatile anesthesia without opioid may be a good choice for minor surgeries, such as thyroidectomy.